Research of Osteoarthritis Based on the Academic Thought of Chen Keji - Xianxiang LIU (康复学报)
Objective:To dig, inherit and carry forward the academic thought of Chen Ke-ji in the treatment of osteoarthritis, and then explore the core pathogenesis and treatment concept of osteoarthritis.Methods:Carrying out the basic theory, clinical application and development research by reading scholarly works, such as Medical Selection of Chen Keji, Academic Thought and Medical Record of Chen Keji, Medical Records of Qing Dynasty Palace, listening to Chen Keji's words.Results:(1) The basic pathological characteristics of osteoarthritis are articular cartilage degeneration, hyperosteogeny is followed by. The clinical manifestation of articular cartilage degeneration is wilting syndrome, and the clinical manifestation of hyperosteogeny is impediment syndrome. The deficiency in origin and excess in superficiality is the core pathogenesis of osteoarthritis. (2) The treatment concept of osteoarthritis should be based on the principle of holistic concept and syndrome differentiation. The principle of treatment is wilting syndrome in origin, and impediment syndrome in superficiality. If in urgency, treats impediment syndrome by expelling wind, eliminating dampness, relieving pain; if in non-urgency, treats wilting syndrome by nourishing liver and kidney, profiting vitality; if longer duration, treats wilting and impediment syndrome together by nourishing liver and kidney, profiting vitality, expelling wind, eliminating dampness and relieving pain. (3) The clinical treatment of osteoarthritis through internally taking Duhuo Jisheng Decoction (modified according to wind, cold, dampness, phlegm and blood stasis), fumigating and washing formula, Datura stramonium gel for external application and family physiotherapy by knee arthritis therapeutic apparatus (KATA).Conclusion:Forming a new treatment concept of osteoarthritis, which is based on the idea that the core pathogenesis of osteoarthritis is deficiency in origin and excess in superficiality.